Development of a multi-agent system for operational management of Smart City housing and communal services resources in real time - Akhayeva, Ж.Б.; Zakirova, А.Б.; Tolegenova, Г.Б.; Aldasheva, Л.С. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2023)
The principles of the development of a multi-agent system designed to manage the resources of the housing and communal services of a Smart city in real time are described. The multi-agent system provides the ability to flexibly respond to unforeseen events arising in the working process, which allows you to plan, optimize and monitor the work of personnel and housing and communal services equipment in real time. The developed method of adaptive resource planning, the main functions, architecture and interface of the system are presented. It is shown that the introduction of an intelligent system makes it possible to complete the work in optimal time.